Post-marketing safety study to evaluate pregnancy outcomes among recipients of hepatitis B vaccines - Katia J Bruxvoort; Lina S Sy; Jeff Slezak; Bradley K Ackerson; Lei Qian; Sijia Qiu; Zendi Solano; Kristi Reynolds (Human Vaccines & Immunotherapeutics)
HepB-CpG is a licensed adjuvanted two-dose hepatitis B vaccine for adults, with limited data on exposure during pregnancy. We assessed the risk of pregnancy outcomes among individuals who received HepB-CpG or the 3-dose HepB-alum vaccine ≤28 d prior to conception or during pregnancy at Kaiser Permanente Southern California (KPSC). The pregnancy cohort included KPSC members aged ≥18 y who received ≥1 dose of hepatitis B vaccine (HepB-CpG or HepB-alum) at KPSC outpatient family or internal medicine departments from August 2018 to November 2020. We followed these individuals through electronic health records from the vaccination date until the end of pregnancy, KPSC health plan disenrollment, or death, whichever came first. Among 81 and 125 eligible individuals who received HepB-CpG and HepB-alum, respectively, live births occurred in 84% and 74%, spontaneous abortion occurred in 7% and 17% (adjusted relative risk [aRR] 0.40, 95% CI: 0.16–1.00), and preterm birth occurred in 15% and 14% of liveborn infants (aRR 0.97, 95% CI 0.47–1.99). No major birth defects were identified through 6 months of age. The study found no evidence of adverse pregnancy outcomes for recipients of HepB-CpG in comparison to HepB-alum.